Mycobacterium bovis Bacille-Calmette-Guérin Infection Aggravates Atherosclerosis - Huaman, Moises A. (Front Immunol, 2020)
Tuberculosis has been associated with increased risk of atherosclerotic cardiovascular disease. To examine whether mycobacterial infection exacerbates atherosclerosis development in experimental conditions, we infected low-density lipoprotein receptor knockout (Ldlr (-/-)) mice with Mycobacterium bovis Bacille-Calmette-Guérin (BCG), an attenuated strain of the Mycobacterium tuberculosis complex. Twelve-week old male Ldlr (-/-) mice were infected with BCG (0.3–3.0x10(6) colony-forming units) via the intranasal route. Mice were subsequently fed a western-type diet containing 21% fat and 0.2% cholesterol for up to 16 weeks. Age-matched uninfected Ldlr (-/-) mice fed with an identical diet served as controls. Atherosclerotic lesions in aorta were examined using Oil Red O staining. Changes induced by BCG infection on the immunophenotyping profile of circulating T lymphocytes and monocytes were assessed using flow cytometry. BCG infection increased atherosclerotic lesions in en face aorta after 8 weeks (plaque ratio; 0.021±0.01 vs. 0.013±0.01; p = 0.011) and 16 weeks (plaque ratio, 0.15±0.13 vs. 0.06±0.02; p = 0.003). No significant differences in plasma cholesterol or triglyceride levels were observed between infected and uninfected mice. Compared to uninfected mice, BCG infection increased systemic CD4/CD8 T cell ratio and the proportion of Ly6C(low) non-classical monocytes at weeks 8 and 16. Aortic plaque ratios correlated with CD4/CD8 T cell ratios (Spearman’s rho = 0.498; p = 0.001) and the proportion of Ly6C(low) non-classical monocytes (Spearman’s rho = 0.629; p < 0.001) at week 16. In conclusion, BCG infection expanded the proportion of CD4(+) T cell and Ly6C(low) monocytes, and aggravated atherosclerosis formation in the aortas of hyperlipidemic Ldlr (-/-) mice. Our results indicate that mycobacterial infection is capable of enhancing atherosclerosis development.